Incidencia de infecciones de trasmisión sexual en adolescentes atendidas en el Centro de Salud Brisas del Mar desde septiembre del 2009 hasta marzo del 2010 - Crespo Azanza, Gabriela E. (2011)
The main objective of this thesis was to determine the incidence of ITS in adolescents. A cross-sectional descriptive study was conducted among adolescents who were treated at the health center Brisas del Mar from September 2009 to March 2010. The information was obtained through a survey that is attached to each patient’s medical history.